2017
DOI: 10.1002/cbin.10767
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells promote regeneration of damaged neuron cells on the cellular model of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disease and many types of stem cells have been used in AD therapy with some favorable effects. In this study, we investigated the potential therapeutical effects of human dental pulp stem cells (hDPSCs) on AD cellular model which established by okadaic acid (OA)-induced damage to human neuroblastoma cell line, SH-SY5Y, in vitro for 24 h. After confirmed the AD cellular model, the cells were co-culture with hDPSCs by transwell co-culture system till 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…To further explore whether hUC‐MSCs could restore damaged neural cells, we used an in vitro AD cell model of tauopathy induced by okadaic acid (OA) which we have established in a previous work. [ 19 ] According to different sensitivities to OA, primary neurons and SH‐SY5Y cells were induced by incubation with OA at a final concentration of 10 n m for 4 h and 20 n m for 24 h (Figure S3, Supporting Information). We analyzed the cell morphology, mitochondrial function, cell viability, subcellular structure and phosphorylation level of tau protein to assess the degree of damage induced by OA and the restorative effects with conditioned medium (CM) of hUC‐MSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore whether hUC‐MSCs could restore damaged neural cells, we used an in vitro AD cell model of tauopathy induced by okadaic acid (OA) which we have established in a previous work. [ 19 ] According to different sensitivities to OA, primary neurons and SH‐SY5Y cells were induced by incubation with OA at a final concentration of 10 n m for 4 h and 20 n m for 24 h (Figure S3, Supporting Information). We analyzed the cell morphology, mitochondrial function, cell viability, subcellular structure and phosphorylation level of tau protein to assess the degree of damage induced by OA and the restorative effects with conditioned medium (CM) of hUC‐MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37,38 ] Here, we used an in vitro AD cell model of tauopathy induced by OA which is a classic method to study tau diseases in vitro [ 39,40 ] that we have established in previous work. [ 19 ] By using this model, we demonstrated that hUC‐MSCs could effectively recover and rescue OA‐induced neurological damage, including improving cytoskeleton arrangement and mitochondrial function, restoring dendritic length and dendritic spines number, and partially inhibiting tau hyperphosphorylation (Figure 3 and Figure S4, Supporting Information). Through in vivo and in vitro models, we have more comprehensive evidence that hUC‐MSCs could effectively treat AD, at least partially by regulating tau hyperphosphorylation.…”
Section: Discussionmentioning
confidence: 98%
“…Because a definitive cure has not been reached so far, stem cell therapies have been investigated for their usefulness in rescuing or even preventing neural loss in patients with AD (Brookmeyer et al, ). Clinical trials are currently ongoing, and various preclinical studies have been performed using AD animal models (Kim et al, ; Li et al, ; Wang et al, ; Zhang et al, ). Ahmed et al studied the therapeutic potential of secretome derived from DPSCs to decrease apoptosis and cytotoxicity mediated by amyloid β peptide (Ahmed, Murakami, Hirose, & Nakashima, ).…”
Section: Dpscs and Neurological Diseasesmentioning
confidence: 99%
“…For a deep investigation of AD treatments, AD mouse models have been created by overexpression amyloid precursor protein. Okadaic acid (OA)-induced SH-SY5Y cells present a rounder shape with retracted cytoplasm and poor adherence 70. AD cell model is also frequently used in researches.…”
mentioning
confidence: 99%
“…Okadaic acid (OA)-induced SH-SY5Y cells present a rounder shape with retracted cytoplasm and poor adherence 70. Apart from the above-mentioned mechanisms, DPSCs possess the ability to promote neural repair in in vitro AD model 70. Several MSCs, including BMSCs and ADSCs, have been proven to be beneficial in AD recovery 71.…”
mentioning
confidence: 99%